2018
DOI: 10.2174/1745017901814010154
|View full text |Cite
|
Sign up to set email alerts
|

Quick Identification of the Risk of Psychosis: The Italian Version of the Prodromal Questionnaire-Brief

Abstract: Background:Diagnosing people during the prodromal phase of an incipient psychosis can improve the chance of better outcome. In busy clinical settings, the ideal tool is a brief, easy-to-complete self-report questionnaire.Objective:To test the psychometric properties of the Italian version of one of the most used screening tools for the identification of the risk of psychosis, the Prodromal Questionnaire-Brief (PQ-B).Methods:Cross-sectional design. A convenience sample of college students was enrolled via snowb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The subject recruitment information indicated that Loewy’s study included a large number of subjects referred from the community and primary health care institutions for the evaluation of high-risk groups. Xu’s study, on the other hand, was carried out among general outpatients visiting clinics for various psychological and psychiatric problems, and Preti’s study included general college students [23,26]. It is known that in the diagnosis of groups at high risk for psychosis, enriched samples show a higher prevalence of psychosis high-risk groups compared with non-help-seeking general populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subject recruitment information indicated that Loewy’s study included a large number of subjects referred from the community and primary health care institutions for the evaluation of high-risk groups. Xu’s study, on the other hand, was carried out among general outpatients visiting clinics for various psychological and psychiatric problems, and Preti’s study included general college students [23,26]. It is known that in the diagnosis of groups at high risk for psychosis, enriched samples show a higher prevalence of psychosis high-risk groups compared with non-help-seeking general populations.…”
Section: Discussionmentioning
confidence: 99%
“…Loewy et al [22] modified the original 92-item PQ to create 21-item and 16-item versions with improved accuracy and efficiency, and these shorter versions show higher specificity and equivalent sensitivity than the earlier version. This study used the PQ-B, an effective and efficient self-report rating scale comprising 21 items for screening individuals to identify those at high risk of psychosis [23]. The respondents were asked to answer “yes” if they had experienced the positive symptoms described in the PQ-B’s 21 questions and “no” if they did not.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy individuals may develop psychotic-like experiences (PLEs) as a response to physical isolation and sensory deprivation [ 42 , 43 ]. PLEs such as perceptual disturbances, unusual thinking, suspiciousness, grandiosity, and disorganized communication are prevalent among the general population [ 44 , 45 ], especially among adolescents [ 46 , 47 ]. According to the psychosis proneness persistence–impairment model, PLEs reflect the existence of a “psychosis severity continuum” and are not necessarily associated with the presence of a disorder [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Prodromal Questionnaire-Brief This is the Italian version of the Prodromal Questionnaire-Brief (PQ-B) (Preti et al, 2018), which is a yes/no 21-item self-report questionnaire used to assess positive symptoms experienced in the past month in the general population. For each symptom, responders have to rate the level of distress and its related impairment in everyday life, in a range from 1 (strongly disagree) to 5 (strongly agree), with 4 or 5 indicating distress.…”
Section: ) Launay-slade Hallucinations Scale-extended Revisedmentioning
confidence: 99%